A possible mechanism of Cry7Ab4 protein in delaying pupation of Plutella xylostella larvae - Lu, Jing-Wen; Jin, Liang; Li, Meng-Ge; Yu, Bryan Q.; Wen, Yang-Fan; Gu, Yu-Qing; Lin, Yi; Yu, Xiao-Qiang (Frontiers in Immunology, 2022)
Cry toxins produced by Bacillus thuringiensis (Bt) are well-known for their insecticidal activities against Lepidopteran, Dipteran and Coleopteran species. In our previous work, we showed that trypsin-digested full-length Cry7Ab4 protoxin did not have insecticidal activity against Plutella xylostella larvae but strongly inhibited their growth. In this paper, we expressed and purified recombinant active Cry7Ab4 toxic core from Escherichia coli for bioassay and identification of its binding proteins. Interestingly, Cry7Ab4 toxic core exhibited activity to delay pupation of P. xylostella larvae. Using protein pull-down assay, several proteins, including basic juvenile hormone-suppressible protein 1-like (BJSP-1), were identified from the midgut juice of P. xylostella larvae as putative Cry7Ab4 binding proteins. We showed that feeding P. xylostella larvae Cry7Ab4 toxic core upregulated the level of BJSP-1 mRNA in the hemocytes and fat body, and decreased free juvenile hormone (JH) level in larvae. BJSP-1 interacted with Cry7Ab4 and bound to free JH in vitro. A possible mechanism of Cry7Ab4 in delaying pupation of P. xylostella larvae was proposed.